THE INTERNATIONAL INNOVATIVE UNIVERSITY AS A CENTER FOR THEORETICAL AND TECHNOLOGICAL INNOVATIONS - Lyudmila S. Dovgal’; Olga V. Nepsha (Высшее образование в России)
The article considers the theoretical and methodological platform for development education and training process at the International Innovative University. An integrated system for organization of educational, scientific, research and educational activities at the University is an educational platform for implementation of the most advanced educational technologies.